2015
DOI: 10.1007/s11010-014-2295-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and DNA methylation of angiotensin type 1A receptors in vascular tissues during genetic hypertension development

Abstract: Angiotensin type 1a receptor (AT1aR) is thought to play an important role in the development of hypertension. However, it is unknown how the AT1aR expression in vascular tissue is changed during the development of hypertension or if the degree of methylation in the AT1aR promoter correlates with the expression of AT1aR. To address these questions, we measured AT1aR mRNA, protein expression, and methylation status of the AT1aR promoter in the aorta and mesenteric artery of male spontaneously hypertensive rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…In a previous study, AGTR1 methylation levels were linked with age in rats [Pei et al, 2015]. However, the present study failed to demonstrate such an association between age and CpG methylation (data not shown), and ongoing research is required to investigate this.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In a previous study, AGTR1 methylation levels were linked with age in rats [Pei et al, 2015]. However, the present study failed to demonstrate such an association between age and CpG methylation (data not shown), and ongoing research is required to investigate this.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have shown that AGTR1 promoter hypomethylation is associated with the risk of primary hypertension in rats [Bogdarina et al, 2007[Bogdarina et al, , 2009[Bogdarina et al, , 2010Pei et al, 2015]. The present study hypothesized that an aberrant AGTR1 promoter methylation might also lead to EH in humans.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Pei et al22 reported hypomethylation of the promoter regions of the Ang II type 1a receptor gene in vascular tissues of hypertensive rats. Hypomethylation of the promoter regions of the Ang II type 1b receptor gene in the adrenal glands of the maternal low‐protein rat promoted hypertension through an exaggerated response to salt 23.…”
Section: Discussionmentioning
confidence: 99%